Relación entre el estado nutricional y la depresión en escolares de 8 a 11 años en la ciudad de Loja - Burneo López, Joselyn Carolina (2020)
In Ecuador there is an increase in overweight and child malnutrition, as a consequence of excessive and inadequate food consumption, lack of physical activity and socioeconomic development, leading to serious consequences for children's development, becoming a risk factor that directly influences the child's psychological environment, increasing rates of depression, anxiety and low self-esteem. This research aimed to analyze the relationship between nutritional status and depression in schoolchildren from 8 to 11 years old in the city of Loja, categorize nutritional status and identify schoolchildren diagnosed with depression. A quantitative, probabilistic, randomized and stratified study was carried out, in a population of 294 children who were studying in the different mixed basic education institutions of the urban parishes of the same city and which according to the sampling were: "IV Centenario" school, "José Ángel Palacio" school, “Marieta de Veintimilla” school, “Julio María Matovelle” school, “Graciela Felipa Atarihuana” school, “Juan Pablo ll” private school, “Interandino” school, “San Francisco” school, “Pradera” Municipal school, anthropometric data were taken weight, height and BMI which were recorded in the growth curves of the Ministry of Public Health and the application of the CDI Test or Inventory of Childhood Depression. The following results were reached: 54.4% (n = 160) of children present a normal nutritional state, 42.5% (n = 125) overweight and 3.1% (n = 9) underweight. Regarding depressive symptoms, 71.8% (n = 211) did not present depressive symptoms, 21.1% (n = 62) present mild depression and 7.1% (n = 21) severe depression. In conclusion, there is a statistically significant relationship between nutritional status (overweight) and depression in schoolchildren from 8 to 11 years old in the city of Loja. Keywords: Weight, Height, BMI, Depression, CDI Test or Inventory of Childhood Depression.